BENTUK DAN TANGGUNGJAWAB PIHAK BANK TERHADAP DANA SIMPANAN PARA NASABAH - Fitriah, Fitriah (Faculty of Law, University of Palembang, 2018)
A bank is a financial institution whose existence depends absolutely on the trust of its customers who entrust their savings funds. Banks are very concerned that the trust of the public, who have and who will save their funds, are well-maintained, considering that the bank is part of the financial system and payment system. Bank secrecy is very important because banks need the trust of the people who keep their money in the bank. The customer only entrusts his money to the bank or makes use of the bank's services if the bank provides a guarantee that the bank's knowledge of deposits and the state of their assets will not be misused. The legal relationship between the bank and the depository customer starts from the signing of a written agreement (contractual relationship) between the bank and the customer which contains the rights and obligations for each party. As for the form of agreement for depositing funds between the customer and the bank, it is called a deposit agreement (Article 1319 Civil Code). In a deposit agreement, the bank sets certain general requirements in a deposit account or savings account, among others, the recipient of the deposit (bank) can use the depositors' money and at a certain time the bank will provide interest. Other provisions that can be used as the basis of relations between banks and depositors are Proxy Giving. Depositors give their power to banks when signing deposit accounts or savings accounts or bank accounts. This agreement becomes a law or law for both parties (Article 1338 of the Civil Code). As a manifestation of the bank's responsibility for depositing customers, banks must pay attention to the 4 (four) pillars of the relationship between depositors and banks, namely: Prudence, Health, Bank Secrets and Trust